2012
DOI: 10.1111/j.1557-9263.2012.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass variation in breeding Florida Scrub-Jays

Abstract: Many birds lose mass when feeding dependent young and multiple hypotheses have been proposed to explain this loss. The reproductive-stress hypothesis suggests that mass loss results from an energy deficit. The flight-efficiency hypothesis suggests that breeders lose mass in advance of feeding young to save energy during flight. The reserve-mobilization hypothesis suggests that female breeders accumulate energy reserves during egg production and incubation and mobilize those reserves to meet their own energy ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Their weigh fluctuated and showed some significant difference when comparing different stages or fortnights, but the differences were small (<1 g). The patterns of mass variation for female and male breeders in this study are consistent with mass data for an adjacent study population of the Florida scrub-jay collected over three years during the building, incubation and nestling stages ( Schoech, 1998 ) and to data collected in the same population in different years ( Brand & Bowman, 2012 ). However, in these studies the patterns of mass variation in helpers were never examined in detail before.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Their weigh fluctuated and showed some significant difference when comparing different stages or fortnights, but the differences were small (<1 g). The patterns of mass variation for female and male breeders in this study are consistent with mass data for an adjacent study population of the Florida scrub-jay collected over three years during the building, incubation and nestling stages ( Schoech, 1998 ) and to data collected in the same population in different years ( Brand & Bowman, 2012 ). However, in these studies the patterns of mass variation in helpers were never examined in detail before.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study on long term mass variation for females and males breeders throughout the breeding season showed that both sexes lost mass during the period of nestling care, but not when feeding fledglings. Although post-fledging is a period of peak effort ( Brand & Bowman, 2012 ) this is also the period during which contributions by helpers is at its highest, suggesting that their contributions might buffer mass losses by breeders. Despite this, few studies have examined mass loss in non-breeding helpers of cooperative species.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established in a wide range of animals that reproduction is energetically costly (Gittleman and Thompson 1988, Olsson et al 1997, Watson et al 1998, Hendry and Berg 1999, Ferna´ndez et al 2000, Brand and Bowman 2012. High energy demands are associated with multiple stages of the reproductive cycle, for example the construction of nests (Gauthier and Thomas 1993, Nilsson and Ra˚berg 2001, Mikheyev and Tschinkel 2004, the production of eggs in oviparous species (Fitzpatrick 1973, Vance 1973, Tallamy and Denno 1982, Ve´zina and Williams 2005, brooding and incubating (Fitzpatrick 1973, Tallamy and Denno 1982, Ferna´ndez et al 2000, Hanssen et al 2003, Lardies et al 2004), gestation and lactation in mammals (Gittleman andThompson 1988, Clutton-Brock et al 1989), and care of young until independence in altricial species (Gittleman and Thompson 1988, Daan et al 1990, Steinhart et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…We used field measures of body condition and assays of oxidative status alongside estimates of prospecting effort. Previous studies on Florida scrub-jays have demonstrated mass changes (Brand & Bowman, 2012;Cucco & Bowman, 2018) as well as oxidative damage (Heiss & Schoech, 2012) in relation to breeding season and reproductive effort. However, the relationship between such proxies of body condition and prospecting effort remains unknown owing to limited information on prospecting We hypothesised that prospecting entails physiological costs in Florida scrub-jays, potentially constraining prospecting effort and leading to individual differences.…”
Section: Introductionmentioning
confidence: 95%